Teachers’ strategies in implementing qur’anic tartil to improve students’ qur’an reading skills in madrasah tsanawiyah - Alya Amelia; Nasir (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study addresses the persistent gap between expected Qur’anic reading proficiency and actual student performance in Islamic secondary education, where inaccuracies in pronunciation, inconsistent application of tajwid rules, and limited fluency remain prevalent. Grounded in sociocultural and cognitive learning theories, this research aims to critically examine how tartil-based instructional strategies are implemented and how they contribute to improving students’ Qur’anic reading skills. A qualitative descriptive case study was employed, involving one Qur’an Hadith teacher, 32 students, and two institutional informants. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using an interactive model to ensure analytical depth and rigor. The findings reveal that tartil-based instruction operates as a structured pedagogical cycle consisting of teacher modeling, guided practice, immediate feedback, repetition, and independent recitation. This process leads to significant improvements across four key indicators, namely makhraj accuracy, tajwid application, reading fluency, and tempo control. In addition, continuous corrective feedback and repetitive practice were found to play a central role in strengthening phonological awareness and reading automaticity. Beyond cognitive gains, the study also demonstrates notable affective improvements, particularly in students’ confidence, motivation, and engagement. Importantly, this research advances the conceptualization of tartil as an integrative instructional framework that bridges traditional recitation practices with contemporary pedagogical principles. By providing a process-oriented and context-sensitive analysis, this study contributes to global discussions on religious literacy and instructional design, offering a novel perspective for enhancing Qur’anic education in diverse learning environments.